ORGANIZATIONAL AND ECONOMIC BASIS OF COST FORMATION OF INDUSTRIAL ENTERPRISES IN RUSSIA - Anna R. Plotkina (Statistika i Èkonomika, 2016)
The author makes a factorial analysis of a process of cost formation of industrial enterprises, which revealed and systematized sources of its creation in modern Russian conditions of managing. The management mechanism as the main regulator of financial, production, investment and other development processes of an industrial enterprise is considered in aspect of optimization of its condition.